Simulation of Performance of Heater Treater Using MATLAB - Erwan Adi Saputro; Mirza Aqeel Fernanda; Muhammad Revansyah Ramadhani W (Universitas Muhammadiyah Purwokerto, 2026)
This study presents a comprehensive performance evaluation of Heater Treater operating at oil and gas Field, The unit’s performance was assessed through analytical modeling and MATLAB simulation using field operating data to determine three key parameters: effective length, retention time, and heat duty. The analysis employed established correlations for gravitational settling, residence time, and thermal requirements to compare actual operating conditions with design specifications. The results show that the unit currently operates beyond its design capacity at a throughput of 5600 bbl/day, leading to excessive heat duty (3.9 MMBtu/h > 2.2 MMBtu/h design), insufficient retention time ( 20 min), and inadequate effective length for complete oil–water separation. Optimal performance was achieved only within the flowrate range of 1100–2900 bbl/day, where all parameters remain within safe and efficient limits. The findings indicate that reactivating the preheater and maintaining the optimal operating window would significantly improve dehydration efficiency, reduce thermal load, and extend equipment life.